Selected fluorosubstituted phenyltolanes with a terminal group: NCS, CN, F, OCF3 and their mesogenic and dielectric properties and use for the formulation of high birefringence nematic mixtures to GHz and THz applications. Issue 8 (21st June 2017) - Dziaduszek, J.; Dąbrowski, R.; Urban, S.; Garbat, K.; Glushchenko, A.; Czupryński, K.
ABSTRACT: Thirty laterally fluorosubstituted new 4-isothiocyanato-, 4-cyano-, 4-fluoro- and 4-(1, 1, 1-trifluorometoxy)-4′-(4-alkylphenyl)tolanes have been synthesised and their phase transition temperatures and enthalpies and electric permittivity have been measured. These data have been analysed together with data for earlier prepared similar compounds and with recently prepared analogously substituted 4″-alkyl-terphenyls. It was shown that some di-, tri- and tetra-fluorosubstituted 4-isothiocyanato- and 4-cyano-4′-(4-alkylphenyltolanes) are very useful components for the formulation of high birefringence (Δ n up to 0.5 measured at 589 nm) and large temperature range nematic mixtures for photonic applications, especially in the infra-red, GHz and THz range of electromagnetic radiation. Three ways of formulation of high birefringence mixtures were proposed. GRAPHICAL ABSTRACT: